Evaluation the Efficacy of Ozone and Temperature to Control Mover Stages for Hairy Grain Beetle (khapra) in Laboratory Trogoderma granariumEverts Coleoptera : Dermestidae.) - A. Sabet, Falah; H.Sabr, Saadi (Iraqi Journal of Science, 2023)
The effect of the following treatments were tested on the adult and larval stages of hairy grain beetle Trogoderma granarium (Everts).The treatments were the combination of ozone gaz with high temperatures ( 35، 40 and 45C) and tempreture alone in addition to control treatment. Results showed that (Z+H) and (H) treatments were more lethally effective (100%mortality) than other treatment on larvae and adult stages of insect. The results also showed that first treatment( Z+H) was more effective than the second treatment (H) on two stages ,the temperature alone treatment with 35,40C was not effective on larvae and adults ( male+femal) :while the temperature 45C alone and combined with Ozone gaz was more effective on two stages of insect .It was also found that adult stage was more sensetive to all treatments than larval stage,whereas the late instars larvae was more resistance than middle and early larva instars .the study indicated that insect males were more sensetive than females to the effect of all treatments